IMPLEMENTASI PERATURAN GUBERNUR NOMOR 62 TAHUN 2016 TENTANG KEWAJIBAN PELAYANAN PUBLIK DAN PEMBERIAN SUBSIDI YANG BERSUMBER DARI ANGGARAN PENDAPATAN DAN BELANJA DAERAH KEPADA PERSEROAN TERBATAS TRANSPORTASI JAKARTA - Angel Pricilia Saurina; Yuwanto .; Dzunuwanus Ghulam Manar (Journal of Politic and Government Studies, 2017)
Abstract.Implementation of Public Service Obligation to BUMD PT Transjakarta asgovernment effort to realize good governance and oriented to public service. With thesubsidy, it is hoped that the people can switch to public transportation Transjakarta. Theissues raised in this study: how the implementation of Pergub No. 62 of 2016? And whatare the factors affecting the implementation process of Pergub?The purpose of this study is to understand how the implementation of public serviceobligations to BUMD PT Transjakarta in accordance with Pergub No. 62 of 2016 and thefactors that affect the implementation process.In answering the problems and objectives done by using the theory of goodgovernance, policy implementation is used as one of the formal process to implement apolicy and public service in the field of transportation.The results showed that in the implementation of Pergub No. 62 of 2016 has been implemented in accordance with the mechanism set out in the Pergub that is through the stage of proposal, verification, budgeting and implementation, disbursement, reporting and accountability. In the implementation there are two supporting factors namely disposition that shows the commitment of implementors in implementation and resources both from human resources and finance. Also found two factors that become obstacles implementation are communication and bureaucratic structure.